An analysis of primary school students' scientific literacy - Nasir, Nur Indah Ririn Fitriani; Purwaningsih, Endang; Ekawati, Ratna; Yambi, Tomás de Aquino Caluyua (Univeritas Papua, 2024)
The study aims to analyze the scientific literacy skills of elementary school students. In addition, differences in scientific literacy based on gender were also examined in this study. The study is quantitative and measures students' scientific literacy. Researchers investigated the literacy profile of sixth-grade students in one of the primary schools in Malang City. The target population was 107 sixth-grade students. The sampling technique was saturated, and the population was included in the sample. Data were collected using ten multiple-choice tests. The findings were analyzed by calculating the results of the validity and reliability tests, percentages, mean, and the Mann-Whitney test to calculate the differences in scientific literacy of boys and girls. The results showed that ten items were valid (sig. <0.05), and the reliability was 0.72. The results of the study showed that the less category dominated students' scientific literacy, while only 2.80% achieved excellence. The average total scientific literacy of students was less (45.51). There is no difference in the scientific literacy of girls and boys. It can be concluded from this study that the scientific literacy skills of sixth-grade primary school students are lacking but do not show significant differences between boys and girls. The results of this research are the basis for developing students' scientific literacy in the future by creating appropriate learning.